Does 'Made in Indonesia' Matter? A Study on Brand Origin Perception on Indonesia's Fashion Brand: Case Study Suko - Natawiria, Nikolas Dalle Bimo; Aprianingsih, Atik (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study examines how the country-of-origin (COO) effect influences Indonesian consumers’ purchase intentions toward the local fashion brand SUKO, under Matahari Department Store. Despite SUKO’s competitive strengths broad retail presence in 142 stores across 79 cities and full supply chain control the brand faces a perception-quality gap caused by consumer biases that favor foreign brands. Using a quantitative explanatory approach with PLS-SEM, the research tests a model integrating COO theory, the Theory of Planned Behavior, and the marketing mix (4Ps) to analyze how perceived COO, marketing elements, and product quality shape attitudes and purchase intentions. Data from 230 respondents in Greater Jakarta indicate that reliability and convergent validity are strong across constructs, though HTMT results suggest conceptual overlap between marketing and brand attributes. The structural model identifies which intrinsic and extrinsic cues most influence consumer perceptions and intentions. Theoretically, this research advances COO literature in emerging markets by explaining how attitude toward purchase mediates quality perceptions. Managerially, it provides strategies for Matahari to reduce COO bias and promote SUKO’s credibility. Findings show that most respondents learn about SUKO via social media (Instagram and TikTok) and consist mainly of price-conscious millennials and Gen Z who shop frequently but spend modestly. Recommendations emphasize digital marketing optimization, product quality signaling, and omnichannel integration to strengthen SUKO’s brand positioning in Indonesia’s fast fashion market.